Straining of atomically thin WSe2crystals: Suppressing slippage by thermal annealing - Hu, Wenshuai; Wang, Yabin; He, Kexin; He, Xiaolong; Bai, Yan; Liu, Chenyang; Zhou, Nan; Wang, Haolin; Li, Peixian; Ma, Xiaohua; Xie, Yong (Journal of Applied Physics, 2022)
The atomically thin two-dimensional (2D) transition-metal dichalcogenide (e.g., MoS2) material can withstand large strains up to 11% to change its energy band structure, thereby further tuning its optical, electrical, and other physical properties. However, the slippage of 2D materials on substrate hammers the further strain tuning of the properties of 2D materials. Hereby, a facile three points approach combined with a dry transfer method that can apply uniaxial strain to two-dimensional materials is provided. The slippage of WSe2 on polycarbonate (PC) substrate can be suppressed by thermally annealing WSe2/PC in low pressure Ar atmosphere above 100 °C for 3 h. Straining cycle evolution experiments revealed that the thermal annealing of (1L) WSe2 could suppress slippage from the surface of the PC. The spectral gauge factor of 1L WSe2 is found to be around -60 meV/%. After thermal treatment, WSe2/PC stacking can survive in DI water for at least 24 h without the degradation of the spectral gauge factor. Dome structures are formed after thermal treatments with the interplay of the viscoelasticity and surface tension of the PC and the 0.4% tensile strain on WSe2, and the RMS roughness of WSe2/PC increased from 820 to 1292 pm, indicating that there could be larger lateral friction force to suppress slippage following thermal annealing. Our findings enrich the strain engineering of 2D materials and their device applications.
CRIS-Team Scopus Importer:2022-09-16